Effects of fast-velocity eccentric resistance training on early and late rate of force development - Oliveira, Anderson Souza [UNESP]; Corvino, Rogerio Bulhoes [UNESP]; Caputo, Fabrizio [UNESP]; Aagaard, Per; Denadai, Benedito Sergio [UNESP] (Taylor & Francis Ltd, 2016)
This study examined whether short-term maximal resistance training employing fast-velocity eccentric knee extensor actions would induce improvements in maximal isometric torque and rate of force development (RFD) at early (<100 ms) and late phases (>100 ms) of rising torque. Twenty healthy men were assigned to two experimental groups: eccentric resistance training (TG) or control (CG). Participants on the TG trained three days a week for a total of eight weeks. Training consisted of maximal unilateral eccentric knee extensors actions performed at 180 degrees s(-1). Maximal isometric knee extensor torque (MVC) and incremental RFD in successive 50 ms time-windows from the onset contraction were analysed in absolute terms (RFDINC) or when normalised relative to MVC (RFDREL). After eight weeks, TG demonstrated increases in MVC (28%), RFDINC (0-50 ms: 30%; 50-100 ms: 31%) and RFDREL (0-50 ms: 29%; 50-100 ms: 32%). Moreover, no changes in the late phase of incremental RFD were observed in TG. No changes were found in the CG. In summary, we have demonstrated, in active individuals, that a short period of resistance training performed with eccentric fast-velocity isokinetic muscle contractions is able to enhance RFDINC and RFDREL obtained at the early phase of rising joint torque.
Keywords: Isometric; maximal torque; rate of force development; explosive strength; eccentric training